HJERNEN OG FØLELSER - Gade, Anders (Psyke & Logos, 2022)
Structures in the limbic system constitute the primary cerebral basis for emotions (Gade, 1997), and epileptic activity in these structures results in seizures with emotional content (part 1). These limbic mechanisms have come under increasing cortical control during the phylogenetic development, and two neuropsychological examples of this are provided. Part 2 describes emotional changes in patients with lesions of the right cerebral hemisphere. Part 3 is a review of recent research with analyses of the consequences of lesions in the orbital part of prefrontal cortex. This cortex is closely connected to limbic structures. Emotional changes after lesions of orbitofrontal cortex are accompanied by a deficit in the ability to make sound decisions. Such findings strenghten the view that our ability to make decisions on a purely rational basis is limited, and that emotions play an important role in normal decision making.